Husband Fertility Preferences And Unmet Need for Family Planning on Eligible Couples: Indonesian DHS Analysis 2007 - Nurul Fitriyah (Faculty of Public Health, Andalas University, 2016)
Family planning programs in Indonesia is one of the most successful programs in the world . Achievement of the Contraceptive Prevalence Rate (CPR) has increased until this year. In 1971 Indonesia’s CPR less than 5 % . The numbers continued to rise sharply until 2007, for modern contraception has reached 61.4 %. However, based on data unmet need for contraception exists each year. The objective of this research is to analyze the relationships between husbands fertility preferences and unmet need family planning in Indonesia. This research used 2007 Indonesia Demografi and Health Survei (IDHS) data. Subject of research were monogamous couples. Chi square statistical test and logistic regression test were used with Confidence Interval (CI) 95% and p<0,05. Based on the results of the analysis data found that from 7464 couples, it was 8,1% found unmet need for contraception (wife). Unmet need for contraception (wife) was significantly related to husbands fertility preferences (OR=1,4; CI95%=1,08-1,90), knowledge gap and occupational gap. In conclution, husband fertility preferences were likely to be greater and have more chances of causing wives unmet need for contraception than wife fertility preferences.